Relationship between the rs2596542 polymorphism in the MICA gene promoter and HBV/HCV infection-induced hepatocellular carcinoma: a meta-analysis - Luo, Xiaojun (BMC Med Genet, 2019)
BACKGROUND & AIMS: Various studies have investigated the relationship between the polymorphism, rs2596542, in the promoter of the major histocompatibility complex class I-related gene A (MICA) gene with susceptibility to hepatitis B virus (HBV)/ hepatitis C virus (HCV)-induced hepatocellular carcinoma (HCC); however, the results are inconclusive. This meta-analysis was conducted to investigate the relationship between rs2596542 and HCV/HBV-induced HCC. METHODS: Three electronic scientific publication databases (MEDLINE, Web of Science, and Embase) were screened using specific search terms and relevant literature identified using literature traceability methods. Selected publications were evaluated according to the inclusion and exclusion criteria, and 11 articles were included in the study. Effect size information (odds ratio [OR] and corresponding 95% confidence interval [CI]) were obtained following quality assessment and data extraction from the included publications, and a meta-analysis conducted. RESULTS: A total of 11 publications were included in the study, including 4582 patients with HCC and 21,095 non-HCC patients. TT genotype at rs2596542 was a risk factor for the development of HCC in patients with HCV/HBV infection (OR = 1.248, 95% CI: 1.040–1.499, P = 0.017), particularly those with HCV infection (OR = 1.326, 95% CI: 1.101–1.599, P = 0.003) and Asians (OR = 1.273, 95% CI: 1.002–1.618, P = 0.048), or when the control group was patients with chronic hepatitis C (CHC) (OR = 1.506, 95% CI: 1.172–1.936, P = 0.001). CONCLUSION: The findings of this meta-analysis suggest that the rs2596542 variant in the MICA promoter region may affect MICA and soluble MICA (sMICA) protein expression, thereby influencing physiological vulnerability to HCC cells and the development of HCC. These data provide a theoretical basis for the diagnosis and treatment of patients with HCC and viral hepatitis infection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12881-019-0871-2) contains supplementary material, which is available to authorized users.